2019
DOI: 10.29252/jrh.9.5.401
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy of yoga exercise and intergenerational interaction program on mental health of elderly

Abstract: Wellness is defined as physical, psychological and social wellbeing, not just the lack of disease and physical handicap. This study aimed at comparing the effects of two intergenerational programs and yoga exercises on the mental health of the elderly. The research was based on a quasi-experimental approach with control group and posttest design. The statistical population consisted of Young and old people living. 175 elders were selected using a randomized cluster sampling method and then randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 6 publications
2
9
0
1
Order By: Relevance
“…Also, there was a positive and significant relationship between pain sensation and social support and its dimensions, whereas it had a negative and significant relationship with social support and its dimensions. These findings were in line with other findings [26][27][28].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Also, there was a positive and significant relationship between pain sensation and social support and its dimensions, whereas it had a negative and significant relationship with social support and its dimensions. These findings were in line with other findings [26][27][28].…”
Section: Discussionsupporting
confidence: 94%
“…Theoreticians of this field believe that the person's relationships with others are not considered as social protection unless the individual evaluates them as an appropriate and available source to meet his needs. Social support is significantly associated with life satisfaction [26] and mental health [27]. Although behavioral and psychological factors may not play a salient role in the onset of pain, these factors play a decisive role in the continuing pain and the resulted disability [28].…”
Section: Introductionmentioning
confidence: 99%
“…This may explain why the Hatha yoga group's DASS-21 scores significantly decreased. This is in line with previous findings suggesting that yoga dramatically lowers depressive symptoms and stress levels in older adults [ [37] , [38] , [39] , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have suggested yoga as a mechanism for reducing stress [ [32] , [33] , [34] , [35] ], depression [ 36 ] and anxiety symptoms in older adults (Allen and Steinkohl, 1987). Yoga has been found to significantly reduce depressive symptoms (Krishnamurthy, Telles, 2007 [ [37] , [38] , [39] ]; and stress [ 40 ] in older adults. In fact, yoga has been found to aid in the development of resilience factors (Taylor, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Kimberlee Bonura has done a significant amount of work in this area and conducted a study to see what effect yoga had on psychological health in older adults; she and her colleagues found that yoga helped reduce symptoms of anger, depression, anxiety and improved general self-efficacy (Bonura and Tenenbaum, 2014). There was also a fascinating and as I can tell unique study to look at intergenerational yoga programs and the work showed that this worked well (Ebrahimi et al, 2019). There has also been work into whether yoga programs can help people's cognitive functions (MacDougall et al, 2015;Hishikawa et al, 2019).…”
Section: Yoga For Elderly Peoplementioning
confidence: 99%